POPULAÇÃO DE PLANTAS E REGULADOR DE CRESCIMENTO AFETANDO A PRODUTIVIDADE DE CULTIVARES DE TRIGO - Fernandes, Eliana Cuéllar (2009)
The maximization of the farm inputs use and an efficient crops management can develop the yield potential for area. With the aim of evaluate the effect of trinexapac-ethyl growth regulator and plants populations in the agronomical characteristics, diseases severity, yield components and yield of wheat cultivars with different resistance to the lodging, three experiments was established in the Farm School of the Ponta Grossa State University, in the year of 2008. The experimental design was complete randomized blocks, in a factorial design 6 x 2 with four repetitions for the three experiments. The treatments consisted of six plants populations (150, 300, 450, 600, 750 and 900 seeds of wheat m-2) and of the use or not of the trinexapac-ethyl growth regulator in the rate of 100 g ha-1, applied between 1 and 2 perceivable knot. The treatments were applied in three experiments that deferred to wheat cultivars of different lodging answers: resistance (OR-1), moderately resistant (BRS 208) and moderately susceptible (Safira). The number of tillers per plant, the foliar area per plant and the stem diameter had diminished with the increase of the plants population, independent of the cultivar. The plant height of the BRS 208 cultivar increased with the plants population increase. The plants height and the length of peduncle, had decreased with the trinexapacethyl application, as well as the lodging percentage in the BRS 208 and OR-1 cultivars. To Safira and OR-1 cultivars the yield was greater with the use of trinexapac-ethyl, but without effects in the BRS 208 cultivar. To Safira and OR-1 cultivars the yield adjustment equation in relation to the plants population was quadratic, occurring an increase of the yield with the increase of the plants population of, until a limit, variable with the cultivar.